Which socio-demographic patterns influence nursing managers’ empowerment perceptions among nurses? An investigatory study : Nursing mangers’ empowerment perceptions - Vitale, Elsa; Calabrò, Antonino; Ilari, Federica; Ercolani, Maurizio; Mea, Rocco; Benedetto, Angelo; Capizzello, Donatella; Lezzi, Alessia; Zacchino, Simone; Marzullo, Mirko; Marzullo, Stefano; Lupo, Roberto (Acta Biomedica Atenei Parmensis, 2022)
Abstract. Aim of the work. Nurses were the most numerous healthcare workers employed in the current Italian healthcare systems. By considering them the driving force of the healthcare systems, the present study aimed to investigate which socio-demographic characteristics in nurses could influence empowerment promoted by their managers, by understanding what socio-demographic characteristics influenced the nursing manager empowerment and could help nursing managers to perform their empowerment approaches by highlighting strengths or weaknesses. Methods. An on-line, observational, multicenter, cross- sectional study was conducted by recruiting a total of 126 nurses. Results. Negative and significant correlations and associations were recorded between all the Empowering Leadership Questionnaire sub dimensions and age (p<.05). Data reported linear and significant associations between all the five sub dimensions of the ELQ and age (p<.05), as younger nurses more perceived their nursing managers’ empowerment presence than their older colleagues, too. Conclusions. Empowerment is a very complex topic in the nursing practice in which managers should be aware of the role of empowerment in promoting work engagement and effectiveness and differential effects on new graduates and more experienced nurses.